Cesar's way : the natural, everyday guide to understanding and correcting common dog problems - Millan, Cesar; Peltier, Melissa Jo. (New York : Harmony Books, 2006)
There are at least 68 million dogs in America, and their owners lavish billions of dollars on them every year. So why do so many pampered pets have problems? In this definitive and accessible guide, Cesar Millanstar of National Geographic Channels hit show Dog Whisperer with Cesar Millanreveals what dogs truly need to live a happy and fulfilled life.
Includes bibliographical references and index.
Keywords: Dogs -- Behavior; Dogs -- Training; Human-animal communication